Taxing top incomes in the emerging world: Economic impact under the microscope - Christopher Axelson; Antonia Hohmann; Jukka Pirttilä; Roxanne Raabe; Nadine Riedel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Rising levels of income inequality and tight government budgets have spurred discussions in many developing nations about how to appropriately tax high-income earners. In this paper, we study taxpayer responses to an increase in the top marginal tax rate in South Africa, drawing on exceptionally rich tax administrative data and a transparent empirical identification design. We establish that treated taxpayers strongly reduce their reported taxable income in response to the tax reform. Taxpayers' responses are driven by both reductions in broad income and increases in tax deductions. While regular labour earnings remain unaffected, we find a marked drop in non-monetary wage components and annual incentive and bonus payments. Linking individual to corporate tax returns, we show that part of the observed response reflects adjustments in real economic activity: South African firms, which employ treated workers, experience a decline in output after the reform.
Keywords: H24; H31; 330; income inequality; taxable income; high-income earners; South Africa; tax reform